1994
DOI: 10.1002/pssb.2221850211
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Spin‐Hamiltonian Parameters for the Low Symmetry Fe3+ Centre in LiNbO3

Abstract: . R u~o w~c z~) (a) X-band EPR spectra of Fe3+ in LiNbO, single crystals at room temperature are analyzed with a spin-Hamiltonian of C, symmetry. First the zero-field splitting (ZFS) parameters b:, bt, b:, and b4 are calculated using the superposition model (SPM). The SPM-ZFS results for Fe3+ at the Nb site agree better with the experimental ones than those for Fe3+ at the Li site. Next the crystal field (CF) parameters are predicted using SPM and two sets of available structural data for LiNbO,. Diagonaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 26 publications
(26 reference statements)
2
13
0
Order By: Relevance
“…The results of calculation using the superposition model (SPM) for zero-field splitting parameters (ZFS) b 0 2 , b 0 4 , b 3 4 and b −3 4 for both above centers in lithium niobate crystals are presented in Refs. [21,22]. Additionally we analyze other axial Fe 3+ center in LiNbO 3 :Fe reported by Malovitchko et al [23].…”
Section: Fe 3+ and Mn 2+ Centers In Lithium Niobate Crystalsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of calculation using the superposition model (SPM) for zero-field splitting parameters (ZFS) b 0 2 , b 0 4 , b 3 4 and b −3 4 for both above centers in lithium niobate crystals are presented in Refs. [21,22]. Additionally we analyze other axial Fe 3+ center in LiNbO 3 :Fe reported by Malovitchko et al [23].…”
Section: Fe 3+ and Mn 2+ Centers In Lithium Niobate Crystalsmentioning
confidence: 89%
“…We are focused on analyzing 6 S state Fe 3+ [21] and Mn 2+ [22] ions in LiNbO 3 . The results of calculation using the superposition model (SPM) for zero-field splitting parameters (ZFS) b 0 2 , b 0 4 , b 3 4 and b −3 4 for both above centers in lithium niobate crystals are presented in Refs.…”
Section: Fe 3+ and Mn 2+ Centers In Lithium Niobate Crystalsmentioning
confidence: 99%
“…However, at the present time there is no satisfactory and quantitative unified explanation for the optical absorption and EPR spectra, and the local structure of Fe 3+ in LiNbO 3 crystal. Further, the reported values of the spin-Hamiltonian (SH) parameters obtained from EPR of Fe 3+ in LiNbO 3 are not uniform because of the different experimental conditions and crystal composition [12][13][14][15][16]. Grachev et al [17] has advanced that the spin-Hamiltonian parameters are dependent on the temperature.…”
Section: Introductionmentioning
confidence: 98%
“…11,12 Transition-metal and rare-earth dopant ions play important roles in most of the applications of LiNbO 3 . Many studies have been performed on Fe 3+ -doped LiNbO 3 crystals, [13][14][15][16][17][18][19][20][21][22][23][24] while only a few studies have investigated LiNbO 3 Co-doped with Fe 3+ and Mg. 25,26 However, it was found that the Fe 3+ ions entered the Li sites, [14][15][16] as well as the Nb sites. 13,14,23,24 This ambiguous site assignment may arise from the very similar environments of the cation sites; both the Li + and Nb 5+ ions lie in slightly distorted O octahedra with a C 3 site-symmetry.…”
Section: Introductionmentioning
confidence: 99%